Guiding the Facial Rejuvenation Journey: Fulfilling the Complete Role of Surgeon and Aesthetic Practitioner - Beaty, Mark M. (Facial Plastic Surgery, 2021)
The facial plastic surgeon's role today includes more than provision of procedural excellence. To provide excellent quality of care effective planning and guidance for patients through the aesthetic journey is needed. Methods for the delivery of this level of care are presented and discussed.
Keywords: facial rejuvenation; facelift; skin resurfacing; volume enhancement; facial plastic surgeon